DEVELOPMENT OF A FOOTBALL PASSING TEST TOOL - Azmi; Bambang Kridasuwarso; Fachrezzy, Fahmy (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This test tool can help coaches and players measure the level of accuracy, speed, and power of their passing. With this test tool, players can track the development of their passing skills over time, making it possible to make necessary training adjustments to improve their game performance. The purpose of the tool is to determine the quality of the accuracy of the player's passing, with a signal of lights on, sound and a timer that runs backwards from 90 seconds. From the results obtained and processed, in the validity test the significance level used 5% so that the rtable used was 0.514. The comparison value of r count and r table can be seen in the table below. If r count > r table means the question is valid, then all 10 questions are stated to be valid. The main hypothesis is if the Cronch's Alpha value is > 0.801 then the questionnaire is reliable, and vice versa if Cronch's Alpha < 0.801 then the questionnaire is not reliable. The Cronch's Alpha value of the questionnaire for testing the effectiveness of the 4 (four) sides (front, back, right and left) football passing test tools in the reliability test was 0.960, so the questionnaire for testing the effectiveness of the 4 (four) sides (front, back, right and left) football passing test tools was declared reliable. The pre-test average was 12.73 and the post-test was 15.20 with a standard deviation of 2.017 and 2.077. It is found in the t-test table with a significance level of 0.05 having Sig. (2-tailed) 0.001. The p-value result Sig. (2 - Sided) <0.05, then the football passing test tools can significantly improve the results of the passing test accuracy. This proves that the football passing test tool created is an effective effort to improve the results of passing accuracy in the sport of football.